Middle East Respiratory Syndrome Coronavirus: A Review - Leila Sarparast; Mohammad Jafar Saffar (Mazandaran University of Medical Sciences, 2015)
Context: Middle East Respiratory Syndrome Coronavirus (MERS-CoV) infection is an emerging human disease that has been reported from the Arabian Peninsula and Middle East countries since 2012. Although zoonotic transmission was postulated, virological and serological finding suggest that the dromedary camels act as the potential reservoirs of MERS-CoV infection to humans. As October 2014, a totally 855 confirmed cases with 333 related deaths were reported to WHO. All cases occurred in or epidemiologically linked to affected countries. The virus ability to induce a pandemic attack is limited. The clinical presentations vary and range from asymptomatic infection to severe respiratory disease and death. However, most severe disease occurs in elderly and in those with underlying conditions. Infection prevention and control measures are critical to prevent the possible spread of MERS-CoV infection is health care facilities and in the community. The WHO encourages all member states to perform surveillance of patients with acute severe respiratory infection and to carefully monitor any unusual patterns. This paper aims to review the current key characteristics of MERS-CoV infection in human and update the WHO recommendations about this illness.